Design and research of stripping tool for live-fired cable based on the distribution network. Issue 1 (1st December 2022) - Shan, Xiaofeng; Guo, Xiang; Han, Xianguo; Tang, Xuming
Abstract: High-voltage live cables are often required to be live-fired in the transformation and maintenance of power grids. The traditional live fire connection operation is mainly manual fire connection, which has great potential safety hazards, the fire connection efficiency is low, and the fire connection quality is uneven. This paper designs and develops a peeling tool based on a 10kV live fire connection operation. In view of the problems of low fire connection efficiency and uneven connection quality of traditional live fire connection tools, hierarchical operation, intelligent control, and instantaneous dynamics simulation based on Anasys Workbench are adopted. The design and development of peeling tools are based on 10kV live connection work. Test experiments show that the live cable stripping tool can realize the live cable stripping operation of 10kV cables and has the characteristics of a high degree of automation and stable fire connection quality.